2018
DOI: 10.1002/rnc.4387
|View full text |Cite
|
Sign up to set email alerts
|

Periodic event‐triggered control for distributed networked multiagents with asynchronous communication: A predictive control approach

Abstract: Summary This paper investigates the periodic event‐triggered control problem for distributed networked multiagent systems with interconnected nonlinear dynamics subject to asynchronous communication. A method of state trajectory estimation for the interconnected neighboring agents over each prediction horizon with guaranteed error bounds is addressed to handle the asynchronous communication. Based on it, a distributed robust model predictive control (MPC) is proposed with a distributed periodic event‐triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Besides, as pointed out in [16], the quadratic form (27) subsumes the relative event-triggered mechanism [40]. The extension of v(t j , t s ) by a constant 1 also allows us to capture the absolute event-triggered mechanism [50] and mixed event-triggered mechanism [8]. More specifically, when Q = Q(q 0 , q 1 ) where…”
Section: Algorithm 1 Aperiodic Event-triggered Control (Aetc)mentioning
confidence: 93%
“…Besides, as pointed out in [16], the quadratic form (27) subsumes the relative event-triggered mechanism [40]. The extension of v(t j , t s ) by a constant 1 also allows us to capture the absolute event-triggered mechanism [50] and mixed event-triggered mechanism [8]. More specifically, when Q = Q(q 0 , q 1 ) where…”
Section: Algorithm 1 Aperiodic Event-triggered Control (Aetc)mentioning
confidence: 93%
“…The event-triggering instant sequences {t i }, k ∈ N, obtained via the triggering condition (15), meet inf k∈N (t i+1 − t i ) ≥ βν 1 .…”
Section: Theoremmentioning
confidence: 99%
“…The event-driven MPC issue for networked control system (NCS) with transmission delays in sensor-controller-actuator channel was studied in [14] and the authors showed that this strategy can significantly reduce the network communication cost without affecting the performance of NCS. A robust event-driven MPC algorithm for perturbed linear distributed systems with input and state constraints, was developed in [15], and the authors employed a tube-based MPC method to guarantee robust constraints on the system state. In [16], the authors investigated the periodic event-driven control issue of distributed networked systems with nonlinear dynamics with asynchronous communication.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there exist some typical control techniques only using sampled data to realize feedback operations such as sampled‐data control (SC) in References 18‐21, event‐triggered control (ETC) in References 22‐25, and periodic event‐triggered control (PETC) in References 26,27. The time‐triggered mechanism of SC allows all the sampled data to be transmitted.…”
Section: Introductionmentioning
confidence: 99%